Measurement of the isolated photon cross section in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. -L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (Elsevier B.V., 2006)
The cross section for the inclusive production of isolated photons has been measured in p (p) over bar collisions at root s = 1.96 TeV with the DO detector at the Fermilab Tevatron Collider. The photons span transverse momenta 23 to 300 GeV and have pseudorapidity vertical bar n vertical bar < 0.9. The cross section is compared with the results from two next-to-leading order perturbative QCD calculations. The theoretical predictions agree with the measurement within uncertainties. (c) 2006 Elsevier B.V. All rights reserved.